2016
DOI: 10.1111/are.13130
|View full text |Cite
|
Sign up to set email alerts
|

DNA fragmentation in blue mussel (Mytilus edulis) sperm: aquaculture and fisheries implications

Abstract: The objective of this study was to assess sperm DNA longevity in blue mussels (Mytilus edulis) using a dynamic assessment of sperm DNA fragmentation (SDF) after sperm activation. Mature blue mussels (n = 57) in Vigo (Galicia, Spain) were obtained, specifically rope farmed blue mussels (n = 38) and wild blue mussels (n = 19). After the sperm collection, a subsample was assessed for SDF (0 h), while the rest of the sample was incubated for 6, 9, 12, 24 and 48 h at 15°C, assessing each time point using the Sperm-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…To date, the development of SCDt in invertebrate species has been limited to the blue mussel, Mytilus edulis (Kjelland et al, 2017) and grassphopper, Chorthippus parallelus (Gosálvez et al, 2010); there is currently no SCDt for any decapod species. Of particular interest is P. monodon, where Feng et al (2016) has recently reported the 3D ultrastructure of highly uncondensed chromatin in the mature sperm nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the development of SCDt in invertebrate species has been limited to the blue mussel, Mytilus edulis (Kjelland et al, 2017) and grassphopper, Chorthippus parallelus (Gosálvez et al, 2010); there is currently no SCDt for any decapod species. Of particular interest is P. monodon, where Feng et al (2016) has recently reported the 3D ultrastructure of highly uncondensed chromatin in the mature sperm nuclei.…”
Section: Introductionmentioning
confidence: 99%